1997
DOI: 10.1111/j.2042-7158.1997.tb06802.x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in [3H]Nimodipine and [3H]Rolipram Binding in the Rat Brain

Abstract: Ageing is associated with changes in neurotransmission which might be correlated with abnormal calcium metabolism. Because there is evidence that nimodipine can enhance the learning abilities of ageing animals and rolipram can enhance the excitability of neurons, providing a functional basis for cognition-enhancing activity, age-related alterations in the binding of voltage-dependent L-type calcium channels and calcium/calmodulin-independent cyclic adenosine monophosphate-selective phosphodiesterase (cyclic-AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Aging is associated with specific impairments of hippocampal function, which is reflected in learning and memory deficit [31,48]. These deficits could be associated with the loss of synaptic contacts [49], silencing of synapses [32,50] or decrease of postsynaptic responsiveness [51] (for review see [52]). This is reflected in deficits in the generation of long term plasticity [31,52,53] as well as alterations in the generation of certain spontaneous oscillatory activities [33].…”
Section: Discussionmentioning
confidence: 99%
“…Aging is associated with specific impairments of hippocampal function, which is reflected in learning and memory deficit [31,48]. These deficits could be associated with the loss of synaptic contacts [49], silencing of synapses [32,50] or decrease of postsynaptic responsiveness [51] (for review see [52]). This is reflected in deficits in the generation of long term plasticity [31,52,53] as well as alterations in the generation of certain spontaneous oscillatory activities [33].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we found that the network activity generated by the OB can be reduced by the application of 30 nM Aβ in slices taken from 3-week-old animals (Figure 3), whereas it was necessary to apply 100 nM Aβ to induce a similar reduction in network activity of hippocampal slices taken from 2-week-old animals [52]. Aging has been associated with loss of synaptic contacts [83,84], silencing of synapses [83-85], or a decrease of postsynaptic responsiveness [83,84,86,87] and synaptic dynamics [68, for review see 87], which is reflected in deficits in the generation of certain spontaneous oscillatory activities [52,88]. It remains to be determined which of these phenomena is responsible for the age dependency of Aβ-induced OB network dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…7, No. 4,2001 central noradrenergic transmission. The hypothesis is that the increase of norepinephrine turnover, induced by rolipram in conjunction with the inhibitory action on cAMP metabolism, induces adaptive changes in central synapses more efficiently, resulting in a rapid onset of antidepressant activity.…”
Section: Antidepressant Effects Of Roliprammentioning
confidence: 99%
“…This effect is due to inhibition of PDE IV-mediated Ca 2+ -dependent cAMP hydrolysis (64). Rolipram also enhanced the excitability of neurons, providing a functional basis for cognition enhancement (4). Unlike conventional antidepressants, rolipram stimulates both the presynaptic and the postsynaptic components of monoaminergic transmission (11).…”
Section: Antidepressant Effects Of Roliprammentioning
confidence: 99%
See 1 more Smart Citation